2015
DOI: 10.1371/journal.pone.0129925
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvent Polarity and DNA-Binding on Spectral Properties of Quaternary Benzo[c]phenanthridine Alkaloids

Abstract: Quaternary benzo[c]phenanthridine alkaloids are secondary metabolites of the plant families Papaveraceae, Rutaceae, and Ranunculaceae with anti-inflammatory, antifungal, antimicrobial and anticancer activities. Their spectral changes induced by the environment could be used to understand their interaction with biomolecules as well as for analytical purposes. Spectral shifts, quantum yield and changes in lifetime are presented for the free form of alkaloids in solvents of different polarity and for alkaloids bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…77 It has been observed that incorporation of methoxy group at 12 th position enhances the anticancer activity of macarpine 78 also, improves its DNA binding. 75 Similarly our observation suggests that substitution of methoxy group at 12 th position of CHE is enhancing the binding affinity towards Pu27.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…77 It has been observed that incorporation of methoxy group at 12 th position enhances the anticancer activity of macarpine 78 also, improves its DNA binding. 75 Similarly our observation suggests that substitution of methoxy group at 12 th position of CHE is enhancing the binding affinity towards Pu27.…”
Section: Discussionsupporting
confidence: 68%
“…12 th position of the benzo[c]phenanthridinium compounds has been found to play crucial role in determining their cytotoxic properties. 72,[75][76][77][78] Mackay et al have reported the inuence of 12-alkoxy group of N-methyl benzo[c] phenanthridinium compounds over their anti cancer activity. They found that non functionalized shorter aliphatic chains as 12-alkoxy group show better anticancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 QBAs share the same skeleton linking several methoxy-or methylenedioxy-substituents and mostly exist as the iminium form (chloride) in plants of Fumariaceae, Papaveraceae, Ranunculaceae, and Rutaceae. 4,5 Considering the presence of reactive iminium group, these compounds are prone to react with nucleophiles by 1,2-addition. 4 Chelerythrine chloride (CHE, Scheme 1), one of the most representative and commercially available QBAs, is mainly isolated from edible and medicinal plants of greater celandine Chelidonium majus L. and M. cordata.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4,5 Considering the presence of reactive iminium group, these compounds are prone to react with nucleophiles by 1,2-addition. 4 Chelerythrine chloride (CHE, Scheme 1), one of the most representative and commercially available QBAs, is mainly isolated from edible and medicinal plants of greater celandine Chelidonium majus L. and M. cordata. 5,6 A variety of reported pharmacological properties of CHE include antitumor, antibacterial, antimicrobial, anti-inflammatory, antiplaque, adrenolytic, and local anesthetic effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Quaternary protoberberine alkaloids (QPA) represent a large class of isoquinoline alkaloids [ 1 , 2 , 3 , 4 ]. They consist of variations of a tetracyclic ring system, a derivate of 5,6-dihydrodibenzo[ a , g ]quinolizinium [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%